Controllability of β-Ga2O3 single crystal conductivity by V doping. Issue 31 (14th July 2022) - Li, Pengkun; Han, Xueli; Chen, Duanyang; Sai, Qinglin; Qi, Hongji
Abstract : Strategy for realizing the tunability of the effective carrier concentration of β-Ga2 O3 single crystals using V as a dopant. Abstract : The introduction of different elements into semiconductors to achieve conductivity control of n-type doping has considerable scientific significance and practical application prospects, which can further promote their extensive application in the field of electronic devices. Herein, a series of V-doped beta-gallium oxide (β-Ga2 O3 ) single crystals with different concentrations were cultivated using the optical floating zone method. The influence of V doping on the structural, electrical, and optical properties of β-Ga2 O3 single crystals was systematically investigated. The characterization results revealed that V-doped β-Ga2 O3 single crystals exhibited superior crystalline quality; moreover, the free carrier concentration increased from 6.9 × 10 16 cm −3 to 6.4 × 10 18 cm −3 and then decreased to 3.1 × 10 16 cm −3 with an increase in the V concentration. The optical transmission of the crystals initially decreased in the infrared region and then increased, which is related to the change in the conductive electrons. The intensities of the two absorption peaks located at approximately 400 nm and 610 nm increased with increasing V doping concentration. From the Raman scattering spectra, the inhibition of V on the [GaII O6 ] octahedral peak intensity became evident with increasing V content. These valuable findings may contribute to the research on β-Ga2 O3 -based electronic and optical devices.